PECULIARITIES OF MNEMOTECHNICS USE WHILE LEXICAL MATERIAL STUDYING IN GERMAN LESSONS - Nataliia V. Rybalka (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2020)
This article analyzes mnemotechnics as a reliable mechanism for memorizing accurate information and language learning in general. The scientific basis of this technique revolves around neurobiology and its impact on learning. The researchers have found out that the more connections and associations can be established between new information and information that already exists in the brain, the higher the brain’s ability to remember this new information. Mnemonics allows you to remember complex words or phrases better and contributes to the quality of the material to be studied. This is especially useful for people who may have difficulty remembering information. It is established that memory is a system that operates according to certain laws and rules. In this case, the brain does not remember the images that arise in the head, and the connections between several images. The generation process is carried out on fixed connections in the presence of appropriate incentives. Depending on the stimulus, either it is a place, a word, a picture or even a letter, there are appropriate methods of mnemotechnics: linguistic method; spatial method; visual method; verbal method and the method of physical reactions. Modern research on memory has clearly shown that mnemonics can be a powerful tool in the study of certain data, such as memorizing a list of specific objects. Mnemotechnics includes many forms that can be used effectively in a variety of subjects and with students of different abilities. It is emphasized that the use of mnemotechnics is necessary, because first of all the theory of mnemonics is implemented in practice and allows you to see a positive result; secondly, the use of mnemotechnics is appropriate in terms of psychological, age, subject-methodological features of students; thirdly, most often mnemonic material finds a response in students’ feedback, promotes the development of their interest in a foreign language studying, activation of thinking, improving performance; fourth, mnemonic material helps save time when learning new words or complex grammatical constructions. The use of mnemotechnics significantly increases the level of storage in memory of learned information in comparison with other teaching methods. Experiments on the use of mnemonic techniques in teaching foreign words show their usefulness. However, learning new words in isolation is useless. Therefore, it is better to use such techniques in the process of contextual study of vocabulary, and their choice depends primarily on the level of knowledge of the students